Improving the Performance of Transparent Conducting Electrodes Based on Cu Nanowires - Mardiansyah, Dedi; Usna, Sri Rahayu Alfitri; Nafisah, Suratun; Harsojo, Harsojo; Hatika, Rindi Genesa (Indonesian Journal of Chemistry, 2024)
The fabrication of transparent conducting electrodes (TCEs) is dominated by indium tin oxide (ITO). Some efforts are being made to find alternative materials as a substitute for ITO. Cu nanowire (CuNWs) is an equivalent candidate as a replacement for ITO but has a weakness that is easily oxidized. In this contribution, we report an increase in the performance of CuNWs, which can reduce the effect of oxidation. In this study, we provide a coating of CuNWs using PVP, PVA, and silver nanoparticles (AgNPs). The morphology, formation structure, and conductivity of CuNWs have been investigated by scanning electron microscope (SEM), X-ray diffraction (XRD), and IV meter. The average length and diameter of the CuNWs were 5.5 μm and 120 nm, respectively. The transparent conducting has a stable conductivity after coating with PVP, PVA and AgNPs. The application of transparent conducting electrodes are sensors, electronic devices, solar cells, and organic light-emitting diodes (OLEDs).